Efforts To Improve Student Activities and Results Using The Guided Inquiry Learning Model In Class IX Students of SMP Negeri 9 Kendari - Fridawati Ramli (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2023)
This study aims to increase student learning activities and outcomes in social studies subjects by applying the guided inquiry learning model. This research was conducted in class IX at SMP Negeri 9 Kendari in the 2019/2020 academic year's odd semester. The subjects studied were students of class IX-10, totalling 35 students, with details of 23 male students and 12 female students. This research was carried out in 2 (two) cycles: (a) planning; (b) implementation of actions; (c) observation; and (d) reflection. The data obtained were analyzed using descriptive statistics. The results showed: (1) the value of student activity with the application of the guided inquiry learning model: in cycle I, there were 7 (20%) students out of 35 getting grades in the outstanding category, increasing in cycle II to 24 (68.57) students in the